SPATIO-TEMPORAL PATTERN AND FACTORS ASSOCIATED WITH TUBERCULOSIS MORTALITY IN A NORTHEASTERN STATE - BRAZIL - George Jó Bezerra Sousa; Bruno Victor Barros Cabral; Antonio Marcílio Silveira Silva; Monalisa Ribeiro Alves; Thatiana Araujo Maranhão; Maria Lúcia Duarte Pereira (Universidade Federal do Paraná, 2022)
Objective: to identify the spatio-temporal pattern of tuberculosis mortality and its related factors. Method: ecological study, using as unit of analysis the municipalities of the state of Ceará, Brazil, during the period from 2001 to 2017. Tuberculosis mortality was analyzed by temporal and spatial analysis techniques. Results: in the period, 1,513 deaths from tuberculosis were reported. An average annual increase of 15% in mortality was detected (95% Confidence Interval: 6.2 - 24.6). The indicators that most influenced mortality were life expectancy at birth (β=3.38), households with inadequate water supply and sanitation (β=-0.01) and probability of survival to 60 years (β=-2.26). Conclusion: this study evidenced the increase in the temporal pattern of tuberculosis mortality over the years. Care strategies aimed at treatment adherence and public health strategies aimed at improving the environment of the population should therefore be emphasized.